Practices in social ecological research : interdisciplinary collaboration in 'adaptive doing' /: interdisciplinary collaboration in 'adaptive doing'. (2020) - Rawluk, Andrea; Beilin, Ruth; Bender, Helena; Ford, Rebecca
No abstract available